2020
DOI: 10.1016/j.yhbeh.2020.104708
|View full text |Cite
|
Sign up to set email alerts
|

Females adjust maternal hormone concentration in eggs according to male condition in a burying beetle

Abstract: In birds and other vertebrates, there is good evidence that females adjust the allocation of hormones in their eggs in response to prenatal environmental conditions, such as food availability or male phenotype, with profound consequences for life history traits of offspring. In insects, there is also evidence that females deposit juvenile hormones (JH) and ecdysteroids (ESH) in their eggs, hormones that play a key role in regulating offspring growth and metamorphosis. However, it is unclear whether females adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Multigenerational effects in burying beetles (genus: Nicrophorus) are well established [11,33,52,[65][66][67][68]. Most of these studies investigate the relationship between maternal size and offspring size [11,33,52,65,66,73].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Multigenerational effects in burying beetles (genus: Nicrophorus) are well established [11,33,52,[65][66][67][68]. Most of these studies investigate the relationship between maternal size and offspring size [11,33,52,65,66,73].…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies in burying beetles have demonstrated multigenerational effects on offspring body size. For example, larger offspring being produced on larger carcasses [ 33 , 65 ], larger mothers laying larger eggs, which hatch into larger offspring [ 11 ], young mothers producing smaller offspring [ 66 ], mothers producing smaller offspring when the male parent is present [ 52 ], mothers altering hormone concentration in eggs [ 67 ], and mothers changing egg laying and offspring care behaviors when deprived of food [ 68 ]. Body size of the parent and carcass size are dominant mechanisms through which multigenerational effects are transmitted in burying beetles.…”
Section: Introductionmentioning
confidence: 99%